A preliminary study on diagnosing learning difficulties in cell division topic for mGBL design and development - Han Cheng, Low; Fitri Suraya, Mohamad; Aazani, Mujahid; Rehman Ullah, Khan (Elsevier Ltd., 2025)
STEM education is crucial for equipping students with 21st-century skills to tackle modern challenges. Within STEM, Biology is often regarded as one of the most challenging subjects, with Cell Division being particularly difficult to learn. This preliminary study aimed to explore the challenges faced by secondary school students in Malaysia while learning the Cell Division topic and to identify potential solutions for enhancing learning of the topic from both students' and teachers' views. The ultimate goal is to develop a mobile game-based learning (mGBL) application that can effectively address these challenges. A mixed-methods approach was employed, involving online interviews with three experienced Biology teachers and self-administered questionnaires completed by thirty-one Form 4 students. The results revealed that students struggle to learn the Cell Division topic due to cognitive, motivational, affective, and social perspectives. The cognitive perspective was the most dominant, with students struggling to memorize content, grasp abstract concepts, and differentiate between similar terms. Both students and teachers suggested strategies to enhance learning, including using games, visual learning materials, memory aids, and collaborative learning, which could serve as references for mGBL design. Based on the findings, an mGBL design proposal was formulated to address the identified learning challenges in Cell Division topic, which will guide the development of an mGBL solution in future study.